EFEKTIVITAS TEKNIK REINFORCEMENT TERHADAP PENURUNAN PROKRASTINASI AKADEMIK SISWA - Gita Cahyani Rahmadani; Alfiandy Warih Handoyo; Putri Dian Dia Conia (STKIP Subang, 2026)
Academic procrastination is a behavior characterized by delaying the completion of academic tasks, which can lead to lower academic achievement, increased stress, and reduced student responsibility toward school assignments. This study aimed to examine the effect of the behavioral modification technique using the reinforcement method in reducing academic procrastination among eleventh-grade students at SMA Negeri 10 Tangerang Regency. The study employed a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design. The sample consisted of 10 students, divided into an experimental group of 5 students and a control group of 5 students. Data were collected using an academic procrastination questionnaire that had been tested for validity and reliability. Data analysis was conducted through normality, homogeneity, and Mann–Whitney U tests. The results showed an Asymp. Sig. (2-tailed) value of 0.008, which was lower than 0.05, indicating that H₀ was rejected and H₁ was accepted. These findings demonstrate that the behavioral modification technique using the reinforcement method has a significant effect on reducing students’ academic procrastination. Furthermore, the N-Gain analysis revealed that the experimental group achieved an average gain score of 42.06%, whereas the control group obtained only 1.55%. Therefore, the reinforcement technique can be considered an effective guidance and counseling strategy for reducing academic procrastination among students.